Optimalisasi Manajemen Kelas Berbasis Kolaborasi Dosen Dan Mahasiswa Dalam Meningkatkan Efektivitas Pembelajaran Pengantar Studi Islam Bagi Mahasiswa PI Semester 1 - Annas Marzuqi; Moh. Agus Harisuddin Masrof; Moh. Irmawan Jauhari (PT. Hasba Edukasi Mandiri, 2025)
Education is a strategic process largely determined by the quality of educators in designing, managing, and guiding the learning process. This study aims to analyze the optimization of classroom management through collaboration between lecturers and students to improve the effectiveness of Introductory Islamic Studies learning for first-semester students in the islamic psychology Education (PI) Study Program at Tribakti Islamic University. The need for participatory and adaptive classroom management is crucial given the characteristics of today's generation of students who demand more dialogic interactions. Using a descriptive-qualitative approach through observation, interviews, and documentation, this study found that collaborative-based classroom management can create a more interactive and conducive learning environment and increase student motivation and discipline. This collaboration also strengthens learning responsibility and improves two-way communication, resulting in increased understanding of the Introductory Islamic Studies material. This demonstrates that collaborative classroom management is an effective strategy for improving the quality of learning processes and outcomes in Islamic higher education institutions.